Niels Hørlück Jessen, Anders Myrtue, Per Grau Møller og Erland Porsmose (red.): Landdistrikterne 1950-2050. (Odense Universitetsforlag, 1997). 155 s., 175 kr. - Lind Haase Svendsen, Gunnar (Historie/Jyske Samlinger, 1999)
-